An isotropic zero thermal expansion alloy with super-high toughness - Yu, Chengyi; Lin, Kun; Zhang, Qinghua; Zhu, Huihui; An, Ke; Chen, Yan; Yu, Dunji; Li, Tianyi; Fu, Xiaoqian; Yu, Qian; You, Li; Kuang, Xiaojun; et al. (Nature communications, 2024)
Zero thermal expansion (ZTE) alloys with high mechanical response are crucial for their practical usage. Yet, unifying the ZTE behavior and mechanical response in one material is a grand obstacle, especially in multicomponent ZTE alloys. Herein, we report a near isotropic zero thermal expansion (α l = 1.10 × 10 −6 K −1 , 260–310 K) in the natural heterogeneous LaFe 54 Co 3.5 Si 3.35 alloy, which exhibits a super-high toughness of 277.8 ± 14.7 J cm −3 . Chemical partition, in the dual-phase structure, assumes the role of not only modulating thermal expansion through magnetic interaction but also enhancing mechanical properties via interface bonding. The comprehensive analysis reveals that the hierarchically synergistic enhancement among lattice, phase interface, and heterogeneous structure is significant for strong toughness. Our findings pave the way to tailor thermal expansion and obtain prominent mechanical properties in multicomponent alloys, which is essential to ultra-stable functional materials. Zero thermal expansion materials play an increasingly important role in modern high-precision applications, but they are relatively scarce. Here, the authors achieve an isotropic zero thermal expansion with a very high toughness by manipulating chemical partitioning in chemically complex alloys.